Phase I trial of total marrow and lymphoid irradiation transplant conditioning in patients with relapsed/refractory acute leukemia - Stein, Anthony (Biol Blood Marrow Transplant, 2017)
Current conditioning regimens provide insufficient disease control in relapsed/refractory acute leukemia (AL) patients undergoing hematopoietic stem cell transplantation (HSCT) with active disease. Intensification of chemotherapy and/or total body irradiation (TBI) is not feasible because of excessive toxicity. Total marrow and lymphoid irradiation (TMLI) allows for precise delivery and increased intensity treatment via sculpting radiation to sites with high disease burden or high risk for disease involvement, while sparing normal tissue. We conducted a phase I trial in 51 patients (age: 16–57 years) with relapsed/refractory AL undergoing HSCT (matched related, matched unrelated, or one-allele mismatched unrelated) with active disease, combining escalating doses of TMLI (range 1200–2000 cGy) with cyclophosphamide (CY) and etoposide (VP16). The maximum tolerated dose was declared at 2000 cGy since TMLI simulation studies indicated that >2000 cGy might deliver doses toxic for normal organs at or exceeding those delivered by standard TBI. The post transplant non-relapse mortality (NRM) rate was only 3.9% (95% CI: 0.7–12.0) at day +100 and 8.1% (95% CI: 2.5–18.0) at one year. The cumulative incidence of grade II–IV acute GVHD was 43.1% (95% CI: 29.2–56.3) and for grade III–IV was 13.7% (95% CI: 6.9–27.3). The day +30 complete remission rate for all patients was 88% and was 100% for those treated at 2000 cGy. The overall one-year survival was 55.5% (95% CI: 40.7–68.1). The TMLI/CY/VP16 conditioning regimen is well tolerated at TMLI doses up to 2000 cGy with a low 100 day and 1 year NRM rate and no increased risk of GVHD with higher doses of radiation.